Revitalisasi Tari Tayung Raci Desa Raci Kulon, Kecamatan Sidayu, Kabupaten Gresik - Dwi Zahrotul Mufrihah (Institut Seni Indonesia Yogyakarta, 2019)
Tayung Raci dance is the original art of Raci Kulon village, Sidayu district, Gresik regency, which has been experienced apparent death 27 years. Meanwhile, Tayung Raci Dance begin to reappear sometime around 2014. The form of presenting Tayung Raci dance experience a change that is used to maintain its exclusion as the original art of Raci Kulon village. The change does not leave a culture that has became the identity of Tayung Raci Dance adapt to the community. This is called the revitalization effort that serves as one way of cultural preservation. The formulation of the research problem is how to revitalize Tayung Raci dance, Raci Kulon village, Sidayu district, Gresik regency. The objective of this research is to know the revitalization of Tayung Raci dance, Raci Kulon village, Sidayu district, Gresik regency. This research uses qualitative approach for the case of this study. The results of revitalization research take place in the form of presentation of Tayung Raci dance. The form of presentation are the presentation plot, motion, clothing, property, and music. Revolutions are divided into 5 rounds with some motion. The dress code has a symbolic meaning of dress or soldier’s uniform. The property consists of Wijil Trunojoyo spear, horses, Ketekan mask, Wedokan mask, Macanan mask and Pecut. Musical instruments use drums, Kenong and Tanjidor (drum), slompret and gong with the lyrics of songs use Sholawat Nabi.Keywords: revitalization; Tayung Raci dance; arts of Gresik district